1997
DOI: 10.1164/ajrccm.156.5.9611052
|View full text |Cite
|
Sign up to set email alerts
|

Smoker's Lung Transplanted to a Nonsmoker

Abstract: Alveolar macrophages (AM) from smokers contain characteristic smoker's inclusion bodies within the cytoplasm as a result of ingestion of substances in the inhaled smoke. How long these smoking-related changes in the AM population can be seen after smoking cessation is largely unknown. We had the unique opportunity to investigate a 51-yr-old never-smoker after single lung transplantation (TX) for alpha 1-antitrypsin deficiency emphysema who received a donor's lung from a heavy cigarette smoker. Serial bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Under conditions of supplemental oxygen exposure (acutely ill patients), macrophages can be exposed to up to 90% oxygen. It is known that macrophages exposed to one type of oxidant stress, cigarette smoke, survive for prolonged periods of time in the lung (10). The prolonged life of the macrophages of smokers compared with our previous observations on the cell cycle effects of hyperoxia (hyperoxia induces macrophage cell cycle arrest accompanied by induction of p21 Cip1 and activation of the retinoblastoma protein (11)) suggests the activation of one or more survival pathways by hyperoxia.…”
mentioning
confidence: 49%
“…Under conditions of supplemental oxygen exposure (acutely ill patients), macrophages can be exposed to up to 90% oxygen. It is known that macrophages exposed to one type of oxidant stress, cigarette smoke, survive for prolonged periods of time in the lung (10). The prolonged life of the macrophages of smokers compared with our previous observations on the cell cycle effects of hyperoxia (hyperoxia induces macrophage cell cycle arrest accompanied by induction of p21 Cip1 and activation of the retinoblastoma protein (11)) suggests the activation of one or more survival pathways by hyperoxia.…”
mentioning
confidence: 49%
“…It is known that pulmonary macrophages may persist for many years within the lung, since donor macrophages can be detected 2-3 years following transplant 36 ; however, specific identification of these long-lived, resident cells in an individual that has not undergone transplant is difficult. Rodent studies of pulmonary macrophage depletion suggest that Chana 16 macrophages repopulate the lung rapidly 37,38 and this turnover is increased following infection 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, programmed cell death is observed in various cells and influences the viability of cells in the lung [2325]. However, the AMs of smokers reportedly survive longer than those of non-smokers [26,27]. We previously demonstrated that over-expression of MafB enhanced cell viability following treatment with CSE as well as significantly inhibiting caspase-3 activity and reducing macrophage apoptosis [6].…”
Section: Discussionmentioning
confidence: 99%